Self-Efficacy as an Intrapersonal Predictor for Internal Whistleblowing: A US and Canada Examination - MacNab, Brent R. (Journal of business ethics, 2008)
Examining intrapersonal factors theorized to influence ethics reporting decisions, the relation of self-efficacy as a predictor of propensity for internal whistleblowing is investigated within a US and Canadian multi-regional context. Over 900 professionals from a total of nine regions in Canada and the US participated. Self-efficacy was found to influence participant reported propensity for internal whistleblowing consistently in both the US and Canada. Seasoned participants with greater management and work experience demonstrated higher levels of self-efficacy while gender was also found to be influential to self-efficacy. These individual traits, although related to self-efficacy, did not directly relate to propensities for internal whistleblowing. The findings demonstrate that self-efficacy could represent an important individual trait for examining whistleblowing issues. Internal whistleblowing is becoming an important organizational consideration in many areas of North America, yet there is relatively little research on the topic. Organizations seeking effective internal reporting systems should consider the influence of self-efficacy along with its potential reporting influence. By empirically testing an under-examined component of theory related to internal whistleblowing, this effort contributes to management literature, extending the knowledge beyond a US context, and provides recommendation for managing individual bias with internal reporting systems.